Changes in Sexual Arousal as Measured by Penile Plethysmography in Men with Pedophilic Sexual Interest. (17th March 2014) - Müller, Karolina; Curry, Susan; Ranger, Rebekah; Briken, Peer; Bradford, John; Fedoroff, John Paul
Abstract Introduction Although pedophilia is defined by a recurrent sexual interest in prepubescent children, little attention has been paid to the stability or fluidity of this sexual interest over time. Aim The aim of the current study was to investigate if patterns of penile tumescence (as a proxy for sexual interest) measured by penile plethysmography testing (PPT) can change. Methods In this retrospective chart review study, PPT results of 43 men diagnosed with pedophilia were collected and analyzed. All participants displayed a pedophilic sexual arousal pattern at the time of their first PPT. To test for change, we compared initial PPT results with subsequent PPT results measured at least 6 months later. Main Outcome Measure Sexual arousal was assessed using PPT by measuring change in penile circumference induced by the presentation of standardized sexual audio stimuli. Results Approximately half of the sample (n = 21) displayed a change in PPT results. This change was characterized by a significant decrease of sexual arousal in response to pedophilic (child) stimuli and a significant increase of sexual arousal in response to nonpedophilic (adult) stimuli. No differences between sexual interest changers (ICs) and nonchangers (NC) were found for demographic data or for length of time between assessments. However, between‐group comparisons revealed that ICs had significantly lower pedophilic indices at the initial assessment than NCs. Conclusions Results from the current study indicate that relative pedophilic interest, as defined by increase in penile circumference in response to nonpedophilic stimuli as measured by PPT, changed in about 50% of men diagnosed with pedophilia who also had initial pedophilic PPT sexual responses. This represents a significant challenge to the hypothesis that sexual interest in men with pedophilia is unchangeable and should be the focus of future studies. Müller K, Curry S, Ranger R, Briken P, Bradford J, and Fedoroff JP. Changes in sexual arousal as measured by penile plethysmography in men with pedophilic sexual interest. J Sex Med 2014;11:1221–1229.